1993
DOI: 10.1007/bf01878077
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effects of interleukin 2 and interleukin 7 on the proliferation and autologous tumor cell lysis of tumor-associated lymphocytes

Abstract: Interleukin-7 (IL-7) has an ability to stimulate the proliferation of pre-B cells. It has been shown that IL-7 can also activate T lymphocytes. We here demonstrate that IL-7 in combination with interleukin-2 (IL-2) can drive cell proliferation and enhance the autologous tumor cell lysis by peripheral blood mononuclear cells (PBMC) and autologous mixed lymphocyte tumor cell culture (MLTC)-derived effector cells (MLTC cells). These synergistic effects of IL-2 and IL-7 on the proliferation and the augmentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, we show that KLH acts together with IL-7 to enhance responses further, both in bulk and after semi-cloning. Since the human CD45RA+CD4+ T cell subset has been found to be the main CD4+ IL-2 producer [14], it is possible that this effect is due to a synergistic action of IL-2 and IL-7, such as that observed for tumor-infiltrating CD3 lymphocytes [21]. Although in bulk cultures the effects of KLH and IL-7 can interact, after semi-cloning , two enhancing mechanisms were identified: a CD4 cell-dependent mechanism for KLH and a CD4 cell-independent effect for IL-7.…”
Section: Discussionmentioning
confidence: 96%
“…However, we show that KLH acts together with IL-7 to enhance responses further, both in bulk and after semi-cloning. Since the human CD45RA+CD4+ T cell subset has been found to be the main CD4+ IL-2 producer [14], it is possible that this effect is due to a synergistic action of IL-2 and IL-7, such as that observed for tumor-infiltrating CD3 lymphocytes [21]. Although in bulk cultures the effects of KLH and IL-7 can interact, after semi-cloning , two enhancing mechanisms were identified: a CD4 cell-dependent mechanism for KLH and a CD4 cell-independent effect for IL-7.…”
Section: Discussionmentioning
confidence: 96%
“…Although we chose IL-7 because of its ability to simultaneously stimulate thymopoiesis, 14,43 increase T-cell proliferation, 44,45 and prolong survival of mature T cells, 46 it was not clear before this study which if any of these functions of IL-7 would be effective in T-cell recovery in ICL. ICL T cells express high levels of activation and proliferation markers 3 and, as recently reported, are prematurely senescent.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia can induce the local downregulation of the interferon-γ (IFN-γ) immune response pathway and thereby inhibit the activation of various mediating factors, such as CD4+/CD25+ regulatory factors (where CD represents a cluster of differentiation), IL-10 and transforming growth factor-b. A study has demonstrated that the phenotype of activated IFN + CD8+ T cells was associated with a 1.8-fold increase in tumor sensitivity to radiotherapy [ 55 ]. Therefore, IFN-γ + CD8+ T cells serve as a bridge between immune and radiotherapy responses, and can produce targeted radiosensitization effects.…”
Section: Discussionmentioning
confidence: 99%